Меотские городища на Кубани - Каменецкий, И.С. (Материалы по археологии, истории и этнографии Таврии, 1998)
Городища, описанию которых посвящена статья, расположены на правом коренном берегу Кубани, между станицами Васюринской и Воронежской, что и определило их название. В перечне Покровского-Анфимова Васюринско- Воронежское городище помещено под № 22. This article gives the description of two hill-forts situated on the right-hand bank of the Kuban river between Vasiurinskaya and Voronezhskaya stanitsas. The distance between the outer moats of the hill-fort was only 35-40 m and due to it the hill-forts had to be closely connected. The first one consists of three parts. The sequence of the growth of the hill-fort was the following: the central part - eastern - western. The areas of the parts are correspondingly: 4370 - 4302 - 8729 m, i.e. the total area of the settlement doubled when a new part was assimilated. We can assume that a new part began to be assimilated when the population became twice as much. Estimations show that to the moment of the downfall of the settlement, its population was 600 peoples. Analogous estimation was done for Vasiurinskay - Voronezhskoe II hill-fort.